Verb-gestural association in referential construction in teaching discourse - Ranieri, Thaís Ludmila da Silva (2023)
This work aims to show the verb-gestural articulation in the referential construction in the teaching discourse. For this, we understanding language use like as practice in a multimodal articulation (NORRIS, 2001; KRESS et al., 2001). In turn, referencing is also seen as a multimodal activity (MORATO, 2001; MONDADA, 2005; BENTES, RIOS, 2005; CUSTÓDIO FILHO, 2011; RAMOS, 2012, RANIERI 2015). For that, our research is qualitative and multimodal (NORRIS, 2001; KRESS et al., 2001) with a corpus of videorecorded classes. Our analyzes showed that, in the referential process, verb and gesture are articulated around the resumption of referents in the teacher’s discourse, in view of the discursive, but also didactic aspects.